2015
DOI: 10.1159/000430323
|View full text |Cite
|
Sign up to set email alerts
|

Neuroglobin Plays a Protective Role in Arsenite-Induced Cytotoxicity by Inhibition of Cdc42 and Rac1GTPases in Rat Cerebellar Granule Neurons

Abstract: Background and Aims: We have previously shown that neuroglobin (Ngb) expression can be regulated by sodium arsenite (NaAsO2) exposure in rat cerebellar granule neurons (CGNs). However, the precise molecular mechanisms of Ngb action are largely unknown. Ras homolog (Rho) guanosine triphosphatases (Rho GTPases) are involved in the regulation of a number of cellular processes, including cell cytotoxicity. It has been reported that Ngb can act as a guanine nucleotide dissociation inhibitior (GDI) role t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 71 publications
1
8
0
Order By: Relevance
“…These results are in line with previous data showing that, in cultured cells, overexpression of NGB protected against hydrogen peroxide [35]. Cerebellar granule neurons were recently used [36,37] to study NGB in relation to neurotoxic challenges induced by sodium arsenite (NaAsO 2 ). RNA interference technology was used to silence NGB and the results indicated that in silenced cells the NaAsO 2 -induced cytotoxicity was exacerbated, suggesting a protective role for NGB in this pathological condition.…”
Section: Neuroglobinsupporting
confidence: 86%
See 1 more Smart Citation
“…These results are in line with previous data showing that, in cultured cells, overexpression of NGB protected against hydrogen peroxide [35]. Cerebellar granule neurons were recently used [36,37] to study NGB in relation to neurotoxic challenges induced by sodium arsenite (NaAsO 2 ). RNA interference technology was used to silence NGB and the results indicated that in silenced cells the NaAsO 2 -induced cytotoxicity was exacerbated, suggesting a protective role for NGB in this pathological condition.…”
Section: Neuroglobinsupporting
confidence: 86%
“…NGB treatment was able to stabilize mitochondrial membrane potential [34] and NGB overexpression was associated with reduced mitochondrial DNA damage [50]. Furthermore, as a consequence of NGB overexpression, most of the studies reported a significant decrease of death signaling and a downregulation of molecules involved in the apoptotic cascade [32,36,37,42,44,45,50]. …”
Section: Possible Mechanisms Of Ngb Neuroprotectionmentioning
confidence: 99%
“…For example, ZCL278 can restrain the migratory and invasive characteristics of the prostate cancer cell line PC3 in vitro [139]. In addition, it can also prevent the toxicity of sodium arsenite (NaAsO 2 ) on astrocytes and cerebellar granule neurons, encouraging its use to alleviate arsenic poisoning on the nervous system [141,142].…”
Section: Cdc42 and Its Inhibitors In Cancer Therapymentioning
confidence: 99%
“…Additionally, low levels of TUNEL positive cells in NGB transduced cells demonstrated the anti-apoptotic role of NGB in Leydig cells. Knockdown of NGB in neurons increased TUNEL positive cells in arsenite induce toxicity indicating the protective role of NGB against apoptosis (Liu et al 2015). Anti-apoptotic activity was confirmed by gene expression analysis of pro-and antiapoptotic genes including BAX, p53, caspase-3 and Bcl-2.…”
Section: Discussionmentioning
confidence: 80%